2022
DOI: 10.1177/09544119221102814
|View full text |Cite
|
Sign up to set email alerts
|

Micro-CT comparative evaluation of porosity and dentin adaptation of root end filling materials applied with incremental, bulk, and ultrasonic activation techniques

Abstract: The purpose of this study is to investigate the effect of different application methods on the adaptation to dentin and porosity properties of calcium silicate based materials. This study included 72 maxillary canine teeth that had been extracted for various reasons. Following the root canal treatment, root, end resections were performed on the specimens. After the apicectomy, 3 mm deep cavities were created. All materials were mixed according to the manufacturer’s instructions. Retrograde cavities were filled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 32 publications
0
6
1
Order By: Relevance
“…Interestingly, they found a much greater value of CPV% with Biodentine (3.642%) than OPV% [27]. Concerning the CPV% found by us, its value is lower than the findings of some other authors [27,29]. In contrast with our results and all other research, Toia et al [28] reported a minor CPV% of 0.024%.…”
Section: Discussioncontrasting
confidence: 90%
See 4 more Smart Citations
“…Interestingly, they found a much greater value of CPV% with Biodentine (3.642%) than OPV% [27]. Concerning the CPV% found by us, its value is lower than the findings of some other authors [27,29]. In contrast with our results and all other research, Toia et al [28] reported a minor CPV% of 0.024%.…”
Section: Discussioncontrasting
confidence: 90%
“…In general, Biodentine, probably the most tested CS cement, is suggested to be superior to ProRoot MTA and other new bioceramic materials in terms of interfacial gap volume, internal porosity, and total porosity volume percentage [25,[27][28][29][30][31][32]. Only Jardine et al [27] reported a higher rate of porosity with Biodentine than MTA-Angelus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations